2016
DOI: 10.1007/s11856-016-1341-6
|View full text |Cite
|
Sign up to set email alerts
|

Determining Fuchsian groups by their finite quotients

Abstract: Let C(Γ) be the set of isomorphism classes of the finite groups that are quotients (homomorphic images) of Γ. We investigate the extent to which C(Γ) determines Γ when Γ is a group of geometric interest. If Γ1 is a lattice in PSL(2, R) and Γ2 is a lattice in any connected Lie group, then C(Γ1) = C(Γ2) implies that Γ1 ∼ = Γ2. If F is a free group and Γ is a right-angled Artin group or a residually free group (with one extra condition), then C(F ) = C(Γ) implies that F ∼ = Γ. If Γ1 < PSL(2, C) and Γ2 < G are non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 57 publications
0
77
0
Order By: Relevance
“…(A standard argument shows that two finitely generated groups have the same set of finite quotients if and only if their profinite completions are isomorphic.) Bridson, Conder and Reid have answered the corresponding question for Fuchsian groups positively [BCR14], while Long and Reid have given a positive answer to a related question [LR11]. We refer the reader to Section 8 of [Rei13] for a discussion of this and related problems.…”
mentioning
confidence: 99%
“…(A standard argument shows that two finitely generated groups have the same set of finite quotients if and only if their profinite completions are isomorphic.) Bridson, Conder and Reid have answered the corresponding question for Fuchsian groups positively [BCR14], while Long and Reid have given a positive answer to a related question [LR11]. We refer the reader to Section 8 of [Rei13] for a discussion of this and related problems.…”
mentioning
confidence: 99%
“…We note that recently Bridson, Conder and Reid [6] have proved that Δ(l, m, n) ∼ = Δ(l , m , n ) if and only if Δ(l, m, n) ∼ = Δ(l , m , n ).…”
Section: Grothendieck's Theory With Typesmentioning
confidence: 73%
“…Indeed, limit groups are closely related to free groups (for instance, Remeslen-nikov showed that they are precisely the existentially free groups [34]), and are frequently hard to distinguish from them. Bridson, Conder and Reid [6] pointed out that Corollary C, combined with the results of [41], would resolve Remeslennikov's question in this case.…”
mentioning
confidence: 90%